The cross-linking activity of transglutaminase 2 drives α-Synuclein pathology in synucleinopathy models - Kambiz Hassanzadeh; Jun Liu; Jie Zhang; Mohadeseh Abouhosseini Tabari; Santhosh Maddila; M. Maral Mouradian (Proceedings of the National Academy of Sciences, 2026)
Transglutaminase 2 (TG2) is implicated in synucleinopathies including Parkinson’s disease (PD) and dementia with Lewy bodies, as it promotes α-Synuclein (α-Syn) aggregation in vitro, and evidence for its activity is detected in Lewy bodies in human postmortem brains. Additionally, TG2 overexpression exacerbates α-Syn toxicity in double transgenic mice, while TG2 deletion mitigates the phenotype of α-Syn transgenic mice. Considering that TG2 is a multidomain and multifunctional protein, the present study was carried out to confirm that the transamidase activity of TG2 specifically drives its pathogenetic role in synucleinopathies. We generated transgenic mice expressing a catalytically inactive W241A mutant TG2 and compared them with TG2-overexpressing and TG2 knockout mice using the α-Syn preformed fibril (PFF) model. We also examined double transgenic mice coexpressing human α-Syn with either wild-type TG2 or mutant TG2, alongside α-Syn single transgenic controls. 6 mo post–PFF injection, or at 6 mo of age in the double transgenic lines, the exacerbation of the behavioral and neuropathological phenotype seen with TG2 overexpression was lost with mutant TG2 overexpression in both models. Parallel findings were replicated in PD patient induced pluripotent stem cell-derived dopaminergic neurons. These findings indicate that the cross-linking activity of TG2 plays a pivotal role in α-Syn aggregation and toxicity, underscoring its significance as a therapeutic target in synucleinopathies.